2016
DOI: 10.1111/ffe.12476
|View full text |Cite
|
Sign up to set email alerts
|

An extrapolation method to determine the effective notch stress in circular hollow section X‐joints

Abstract: This paper presents an extrapolation method to determine the effective notch stress (ENS) on the weld toes of welded circular hollow section (CHS) X‐joints in‐line with the extrapolation method to determine the structural hot‐spot stress in existing design guidelines. This investigation verifies and extends the recently proposed ENS extrapolation scheme to CHS X‐joints, which elevates significantly the difficulty in generating a weld toe radius along the brace‐to‐chord intersection as required in existing guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Table 1 lists the nonlinear isotropic and kinematic hardening parameters reported by Saiprasertkit et al 46 The selection of 1 mm notch radius aligns with the recommendation in calculating the effective notch stress in the International Institute of Welding 47 and circumvents an infinite nearby stress field in an otherwise sharp weld toe. [48][49][50] Previous researchers [51][52][53][54][55][56] have also demonstrated that realistic welded joints often entail a finite radius at the weld toe, instead of a mathematically sharp toe. N provides a reasonably accurate prediction of the notch stress and strain at the weld toe.…”
Section: Validation Of the Numerical Analysismentioning
confidence: 99%
“…Table 1 lists the nonlinear isotropic and kinematic hardening parameters reported by Saiprasertkit et al 46 The selection of 1 mm notch radius aligns with the recommendation in calculating the effective notch stress in the International Institute of Welding 47 and circumvents an infinite nearby stress field in an otherwise sharp weld toe. [48][49][50] Previous researchers [51][52][53][54][55][56] have also demonstrated that realistic welded joints often entail a finite radius at the weld toe, instead of a mathematically sharp toe. N provides a reasonably accurate prediction of the notch stress and strain at the weld toe.…”
Section: Validation Of the Numerical Analysismentioning
confidence: 99%
“…19 In particular, the effective notch stress method differs from the hot spot stress method in that through the creation of a virtual effective notch, the stress concentration in a welded structure can be interpreted as the stress in the effective notch. [20][21][22][23][24][25][26][27] Effective notch stress is defined as the total stress at the root of the notch, and it is determined by assuming a linear elastic material. The geometrical characteristics of the weld bead make the roots act as a notch where stress is concentrated, resulting in fatigue cracking initiation and reduced fatigue strength.…”
Section: Introductionmentioning
confidence: 99%
“…This method, considering the strength reduction due to notches, was proposed by Radaj et al (2013) and has been widely applied to fatigue assessment of welded joints (Baptista et al, 2017;Marulo et al, 2017;Sonsino et al, 2012). Recently, there are more researches on fatigue evaluation of welded joints using ENSA in various industries (Bruder et al, 2012;Fricke et al, 2009Fricke et al, , 2012Pedersen et al, 2010), and a simplified calculation procedure regarding ENSA was proposed and verified (Pradana et al, 2015(Pradana et al, , 2017a(Pradana et al, , 2017b. However, there is still scanty evidence of fatigue experimental data of largescale welded joints with thick plate (e.g.…”
Section: Introductionmentioning
confidence: 99%